The Relationship of Brand Love, Self-Esteem, Brand Attitude and Brand Loyalty in Facial Care Product Users - Nurhalisha, Elvanda; Astuti, Puji (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Today's consumers not only fulfill basic needs but also prioritize physical appearance, especially facial care, which is a priority to look better. Having healthy, clean and bright facial skin is the dream of every Indonesian woman. Cosmetics companies certainly carry out strategies to provide benefits and benefits to their consumers to produce an increase in Brand Loyalty. The aim of this research is to determine the relationship between Brand Love, Self-Esteem, Brand Attitude and Brand Loyalty among users of facial care products. This research was conducted on 250 female respondents who used Scarlett, Emina and Whitelab products aged 15 - 40 years in the JABODETABEK area. Data collection was obtained through distributing questionnaires online which was carried out from January to February 2023. This research used the Lisrel Structural Equation Model (SEM) to test the research model. The results of this research show that the four hypotheses proposed are acceptable and one hypothesis is unacceptable. Then, the brand attitude variable has the greatest influence on brand love. Meanwhile, the results show that the proposed research hypothesis does not support the existing hypothesis, namely that the brand attitude variable has no influence on brand loyalty. Therefore, this research implies that brand loyalty is an important factor for a business to be able to maintain its business.